Analyzing Explicit and Implicit accidents workplace costs: . (International Journal of Scientific Research and Management (IJSRM), 2022)
Accidents are one of most important phenomena in the production industries and treat the health of the factory workers. Work accidents are a burden for many parties in many ways. Accidents and incidents lead to costs for companies, individual workers, and society. The economic effects of accidents and injuries are not only as financial expenditures, damages or loss of resources, but also there are adverse effects (such as grief ,Loss of major body organs ,…) that are difficult to express in terms of money. Work-related accidents are a major safety and health topic. Every year, workers are faced to accidents in their workplace. This is a huge cost for businesses and a huge cost in terms of human suffering for the victims and their families. Workplace accidents can mean pain and disability and can affect the worker’s life, both in and out of work. According to the contents, it is very important to review and evaluate accidents and their costs. Some researchers have divided costs into, direct and indirect categories. In this study, costs have classified and described as: Explicit and Implicit costs, next has introduced regression model , analyzed and calculated workshop accident.